Off-label use catalogue of tumor anti-angiogenic drugs in China: a narrative review - Yao, Difei; Hu, Yangmin; Weng, Shanshan; Wang, Tiantian; Zhu, Tao; Liu, Lulu; Luo, Huan; He, Wei; Dai, Haibin (Frontiers in Pharmacology, 2025)
BackgroundThe management of off-label use (OLU) is an important aspect of standardizing and promoting the rational use of antitumor drugs. Tumor anti-angiogenic therapy (AAT) is essential in cancer treatment. However, OLU of anti-angiogenic drugs is common in clinical practice. Recognizing and standardizing the OLU of AAT is a significant challenge that needs to be addressed in the clinic.AimWe aim to collect and categorize the OLU of AAT in oncology based on clinical guidelines, providing practical guidance for drug management.MethodsWe established a multidisciplinary expert team to screen and include evidence-based OLU information.ResultsBy organizing the OLU information, it is evident that these 14 drugs of AAT have indications for 33 cancer types (36 items). Among them, 12 (85.7%) have OLU recommendations, totaling 215 items. These OLU recommendations were classified into four major categories. Cancer type is the most common OLU category, with 12 drugs covering 64 cancer types and 155 items. In addition, OLU in therapy lines, regimens, and dosage was identified in 3–4 drugs each. Bevacizumab, the drug most frequently involved in OLU, is associated with 12 cancer types, 3 therapy lines, 6 regimens, and 2 dosage-related OLU items. In addition, lenvatinib, pazopanib, sorafenib, apatinib, and sunitinib also have OLU recommendations for more than five cancer types.ConclusionOur work offers an updated reference for the OLU of tumor AAT and highlights the need for further exploration into specific management measures for OLU in clinical practice.